2010
DOI: 10.1620/tjem.222.303
|View full text |Cite
|
Sign up to set email alerts
|

Association between Subclinical Hypothyroidism and Proliferative Diabetic Retinopathy in Type 2 Diabetic Patients: A Case-Control Study

Abstract: Subclinical hypothyroidism (SCH) is defined as an asymptomatic state characterized by normal serum levels of free thyroxine and elevated serum concentrations of thyrotropin (> 4.0 μ U/ml). The association between SCH and type 2 diabetes has been well established. Proliferative diabetic retinopathy (PDR) that is characterized by neovascularization is a leading cause of visual loss in adults worldwide. However, whether SCH is related to PDR has not been studied. This study thus aimed to evaluate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
19
1
1
Order By: Relevance
“…Previous studies showed that SCH was associated with DR [17,18], while 2 other studies could not find any relationship between SCH and DR [19,20]. Moreover, it was reported that SCH was an independent risk factor for DN [16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that SCH was associated with DR [17,18], while 2 other studies could not find any relationship between SCH and DR [19,20]. Moreover, it was reported that SCH was an independent risk factor for DN [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Furukawa et al [16] considered that SCH was a determinant factor for diabetic nephropathy (DN). Further, 2 reports have shown SCH as a potential factor for increased risk of diabetic retinopathy (DR) [17,18]. However, this relationship between SCH and DR was not found by Ramis et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…16 Some of the study recently demonstrated that diabetic patients with subclinical hypothyroidism have more severe retinopathy than euthyroid patients with diabetes. 17 To the best of our knowledge no studies have been done to estimate the prevalence of thyroid dysfunction in DM patients in New Civil Hospital (NCH), Surat. So, the present study was planned to determine prevalence of thyroid dysfunction in DM patients in this institute with the objective to study the thyroid dysfunction in DM for early detection and to provide guideline about treatment strategy accordingly.…”
mentioning
confidence: 99%
“…13 In the same way, Guang et al in 2010, reported that patients with higher levels of TSH had a significantly higher rate of PDR than patients with lower levels of TSH. 10 Yang et al reported an association between retinopathy and subclinical hypothyroidism, especially sight threatening diabetic retinopathy. They also mentioned that, even euthyroid patients with TSH levels between 2 and <4µIU/ml had a higher rate of sight threatening diabetic retinopathy than those between 0.4 and <2.0µIU/ml (p=0.008).…”
Section: Resultsmentioning
confidence: 99%